FRI0191 Effectiveness of adalimumab in the treatment of rheumatoid arthritis depends on the dose of methotrexate. (23rd January 2014) - Ito, S.; Oh, K.; Unno, M.; Kobayashi, D.; Azuma, C.; Abe, A.; Otani, H.; Ishikawa, H.; Nakazono, K.; Narita, I.; Murasawa, A.
Abstract : Background: In a study on continuation of adalimumab (ADA) therapy in Japan, the concomitant use of MTX with ADA was associated with higher efficacy and treatment retention rate (1 ). In Western countries, the recommended dose of MTX for patients receiving ADA is 15~20 mg/week on average, while the approved dose of MTX combined with ADA in Japan was 8 mg/week and revised in February 2011 on the basis of the results of analysis of the safety and efficacy of MTX to increase up to 16 mg/week (2 ). Objectives: Analyze the efficacy of ADA by the presence/absence of methotrexate (MTX) and its dose in Japanese patients. Methods: Enrolled were 46 patients who started ADA from Jul 2008 to Feb 2012 and were followed for 24 weeks. Mean dose of MTX was 8.6±2.1 mg/week. Pearson's product-moment correlation coefficient was used to assess the correlations between improvement in DAS28-ESR and MTX dose in patients receiving MTX at <8, 8 and >8 mg/week. Results: Mean DAS28-ESR at baseline and week 24 were, respectively, 4.7±1.3 and 2.8±1.2 in 38 patients with MTX and 4.5±1.0 and 4.2±1.5 in 8 patients without MTX, and 53% and 25% of them achieved clinical remission by week 24. Patients who continued ADA by week 24 accounted for 84.2% and 50.0% in patients with and without MTX. In 14 patients receiving MTX at >8 mg/week, DAS28-ESR decreased quickly from 4.5±1.1 at baseline to 3.3±1.0 and 2.4±1.0 at weeks 4 and 24. Clinical remission at week 24 with ADA was significantly greater in patients administered high dose MTX (DAS28-ESR<2.6: 71% and 40% of those receiving MTX at >8 and <8 mg/week). A significant correlation was noted between the improvement in DAS-ESR and MTX dose. Conclusions: Combination with >8 mg/week of MTX maximizes the clinical efficacy of ADA. References: Takeuchi T et al. Effectiveness and safety of adalimumab in Japanese patients with rheumatoid arthritis: retrospective analyses of data collected during the first year of adalimumab treatment in routine clinical practice (HARMONY study). Mod Rheumatol. 2012;22:327-38. The Japan College of Rheumatology and the Institute for Data Analysis. Study of efficacy and safety of methotrexate at more than 8 mg/week: Evaluation of 3 RA patients cohorts (IORRA, REAL and NinJa) https://www.ryumachi-jp.com/pdf/MTXHighdose.pdf [in Japanese]. Disclosure of Interest: S. Ito Grant/research support from: S. Ito has received speaking fee from Abbott Japan Co. Ltd; Eisai Co. Ltd; Mitsubishi Tanabe Pharma Co. Ltd; Asahi Kasei Co. Ltd; Chugai Pharmaceutical Co. Ltd., K. Oh: None Declared, M. Unno: None Declared, D. Kobayashi: None Declared, C. Azuma: None Declared, A. Abe: None Declared, H. Otani: None Declared, H. Ishikawa: None Declared, K. Nakazono: None Declared, I. Narita: None Declared, A. Murasawa: None Declared